2017
DOI: 10.1017/s0033583517000130
|View full text |Cite|
|
Sign up to set email alerts
|

DNA partitions into triplets under tension in the presence of organic cations, with sequence evolutionary age predicting the stability of the triplet phase

Abstract: Abstract. Using atomistic simulations, we show the formation of stable triplet structure when particular GC-rich DNA duplexes are extended in solution over a timescale of hundreds of nanoseconds, in the presence of organic salt. We present planar-stacked triplet disproportionated DNA (Σ DNA) as a possible solution phase of the double helix under tension, subject to sequence and the presence of stabilising co-factors. Considering the partitioning of the duplexes into triplets of base pairs as the first step of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…The base pair stacking free energies for 3-mers were calculated by the sum of the base pair stacking free energies for two consecutive 2-mers (see Equation 1 in the Materials and Methods section). This strategy was used also by SantaLucia et al (Santalucia and Hicks, 2004) and Taghavi et al (2017) and showed reliable accuracies. Currently, base pair stacking free energies for 2-mers have been extensively studied, both theoretically and experimentally.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The base pair stacking free energies for 3-mers were calculated by the sum of the base pair stacking free energies for two consecutive 2-mers (see Equation 1 in the Materials and Methods section). This strategy was used also by SantaLucia et al (Santalucia and Hicks, 2004) and Taghavi et al (2017) and showed reliable accuracies. Currently, base pair stacking free energies for 2-mers have been extensively studied, both theoretically and experimentally.…”
Section: Resultsmentioning
confidence: 91%
“…Although 2-mer base pair stacking has been studied (Warshaw and Tinoco, 1966; Chan and Nelson, 1969; Stokkeland and Stilbs, 1985; Guckian et al, 1996; Aalberts et al, 2003; Huguet et al, 2010), 3-mer base pair stacking is poorly studied, partly due to the limitations of experimental techniques and the computing power of quantum mechanics (Sponer et al, 2013). To calculate the 3-mer base pair stacking free energy, we combined the base pair stacking free energies for the two consecutive 2-mers in the 3-mer (Santalucia and Hicks, 2004; Taghavi et al, 2017):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it is well-established that three-base codon structure of the genetic code contributes to translation efficiency and fidelity and molecular dynamics modeling suggests that charged particles (e.g., ribosomes) interacting with a polymer (e.g., an RNA) via electrostatic forces moves dynamically along the polymer in steps of three monomers [269]. Quite remarkably, there is now increasing evidence that triplets also play a major role in nucleic acid polymer properties and biogenesis which includes the following: (i) Triplets correspond to the width of the minor groove in a double-stranded nucleic acid polymer, and backbone atoms that are in proximity across the minor grove are separated by three nucleotides on the complementary strand [270,271]; (ii) a three-base periodicity has been observed outside coding sequences and provides, for example, specificity for the positioning of the transcription preinitiation complex [272]; (iii) codon bias affects transcription by affecting RNA folding, which favors transcription elongation by reducing pausing and RNA polymerase backtracking [69,[273][274][275]; (iv) intra-and inter-trinucleotide stacking interactions contribute to stabilizing base pairing during the translation process but could have also played a role in replication early in evolution [76]. Collectively, these observations suggest that the three-base genetic code could have been constrained by physical parameters, allowing the simultaneous enhancement of RNA and protein biogenesis [269][270][271]276].…”
Section: Appendix A1 Genome Physical Organization: From Gene Expresmentioning
confidence: 99%
“…Later, it was demonstrated that S-DNA consists of a full umbrella of conformations where the Sladder motif can coexist with short melting bubbles generated especially on AT-rich segments [15]- [21]. Similarly, computer simulations described in atomic detail (and confirmed) the structural appearance of the overstretched and overtwisted form of P-DNA [22].…”
Section: Introductionmentioning
confidence: 96%